Noncovalent spin-labeling of RNA: the aptamer approach. Issue 83 (2nd October 2018) - Saha, Subham; Hetzke, Thilo; Prisner, Thomas F.; Sigurdsson, Snorri Th.
Abstract : In the first example of noncovalent spin-labeling of unmodified RNA, the MG aptamer was used to capture a tetramethylrosamine-based nitroxide spin label with high affinity. Abstract : In the first example of site-directed spin-labeling of unmodified RNA, a pyrrolidine-nitroxide derivative of tetramethylrosamine (TMR) was shown to bind with high affinity to the malachite green (MG) aptamer, as determined by continuous-wave (CW) electron paramagnetic resonance (EPR), pulsed electron–electron double resonance (PELDOR) and fluorescence spectroscopies.